Project: Heuristic-Functional Animated Movie The Boy’s Dream (Number of the First Tenner) - HILČENKO, Slavojlub; MEDIĆ, Branko (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
Animated movie The Boy’s Dream (number of the first tenner), is the latest project of our instructional team that complies with the latest international requirements in order to develop a e-tutoring platform. In addition, especially in accordance to the needs and possibilities of Generations „Z”, and on the other hand the concept of heuristic algorithms stimulates intuition and common sense in children. Furthermore, the targeted group – children of preschool institutions engaged in monitoring and resolving application, the platform requires and develops their functional-logical potential. The project includes an interactive quiz with 12-manipulation tasks, like upgrading animated themes (and on the other hand, generates a report on the performance and their abilities (average scores of the individual, the group and the percentage of correct answers on questions) which will help teachers to better recognize the level of knowledge on this area and problematic places of learning) as well as the methodological manual. The aim of the paper is to present the project for its full implementation we suggest a period of 2 years.